Comparative study of cold compress and liniment treatment as an adjunct to massage therapy for exercise-associated muscle cramps (EAMC) among young athletes in the Philippine setting - Punay, Justine Nicole N. (Animo Repository, 2021)
Exercise-associated muscle cramps (EAMC) is prevalent among athletes during training or competitions where they are subjected to strenuous activities for a prolonged period. To manage this painful condition, health practitioners have used numerous treatment modalities having massage done with adjunct application such as cold compress or liniment. Studies show that it is debatable which combination of treatment modalities is more effective on people affected by EAMC. Hence, this study aimed to present evidence-based data to show if there is a difference in the effectiveness of the two modalities in treating EAMC. A total of thirty-two (32) athletic participants were enrolled in this study and a total of 40 treatment trials were included in the analysis of data. Each participant performed strenuous exercises meant to induce muscle cramps. The onset of muscle cramps was identified using a set criteria. After which, treatment was applied and the length of time that the cramp was resolved was recorded. Determining relief from muscle cramps was based on the characteristic of muscle hardness and the level of pain by using a numerical rating scale. Results showed that though majority of the participants verbalized preference for the ice treatment, analysis of data using one-way ANOVA revealed that there is no evidence to prove that there is a difference in the effectivity among the treatment modalities performed. In conclusion, though all modalities performed were able to relieve the EAMC, the use of adjunct treatment in addition to massage and stretching may have a placebo effect component, which improves the patient's perception of greater efficacy.